2014
DOI: 10.1080/15228967.2014.868983
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Based Recreation, Spirituality and Persons with Disabilities

Abstract: This article synthesizes empirical studies that explain the relationship between nature-based recreation and spirituality for persons with disabilities. In order to describe this relationship, a theoretical model, which includes the components of antecedent conditions, setting, and recreation, is developed. Antecedent conditions include history and current circumstances, motivation, sociodemographic characteristics, and spiritual tradition. Setting components include being in nature, being away to a different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In previous studies, people stayed in a natural environment and green space to which it is applied to relieve stress [14,15]. According to that, people follow NBSs to enjoy leisure in nature, reducing their stress and restoring their attention [16,17], which are affected by the stress that comes from dwelling in urban society [18,19]. MH, emotional WB, SA, and stress are the core factors to help explain customers' post-purchase activity.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, people stayed in a natural environment and green space to which it is applied to relieve stress [14,15]. According to that, people follow NBSs to enjoy leisure in nature, reducing their stress and restoring their attention [16,17], which are affected by the stress that comes from dwelling in urban society [18,19]. MH, emotional WB, SA, and stress are the core factors to help explain customers' post-purchase activity.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, attention restoration theory (ART) is widely used to explain the psychological recovery effect in the natural environment [ 25 , 26 ]. Although several studies based on ART have revealed that the natural environment significantly influences psychological restoration and relaxation [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], few studies have addressed these relationships from the perspective of ACLS. ART is commonly cited to explain the restorative effects of natural environments, as well as stress-reduction theory (SRT) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%